Kampung Ramadhan sebagai Upaya Penguatan Kesehatan Mental, Sosial, dan Spiritualitas Masyarakat melalui Talkshow, Zakat, dan Ibadah - Raisa Berlian; Santoso Santoso; Wahyi Busyro; Deprizon Deprizon; Dwita Razkia; Rika Septianingsih (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2025)
Ramadan is a holy and blessed month for Muslims. During this month, Muslims are obligated to fast from dawn until sunset. In addition, Ramadan provides an opportunity for Muslims to strengthen their faith and piety as well as to enhance social bonds with others. In an effort to enhance faith, piety, and social connectedness, we took the initiative to organize the “Kampung Ramadan” (Ramadan Village) program. Community service activities are an integral part of the Tri Dharma of Higher Education, which demands the active contribution of academic institutions in addressing real-world social issues. Kampung Ramadan, initiated by the Faculty of Islamic Studies at Universitas Muhammadiyah Riau, is a concrete form of spiritually and socially based service during the holy month. Through an interdisciplinary approach presented in a talk show entitled "Mental Health in the Perspective of Psychology, Economics, and Education," this activity aims to provide enlightenment and spiritual-mental reinforcement for the community. In addition, the distribution of zakat and collective worship further strengthens the values of Islamic brotherhood (ukhuwah islamiyah), social solidarity, and the quality of religious observance. This article presents a systematic review of the implementation of the program, the values it embodies, and its overall impact on both the community and the institution.